National and Local Definitions of an Environmental Nuisance: Water Pollution and River Decontamination in Six Urban Areas of Quebec, 1945–1980 - Castonguay, Stéphane; Bernard, Vincent (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2015)
When it created the Water Purification Board in 1961, the Quebec government intended to proceed with a major reorganization of the municipal wastewater treatment and drinking water systems throughout the province. In the following decades, the Department of Municipal Affairs and Environment developed a series of programs and policies for the treatment of wastewater. If water pollution then appeared as a national problem and the subject of a consensual definition, neighbouring communities were facing specific problems that government policies tended to obscure. Our analysis of six municipalities (Drummondville, Sherbrooke, Saint-Hyacinthe, Granby, Trois-Rivières, and Shawinigan) located in three river basins (Saint-François, Yamaska, and Saint-Maurice), each with its own topography and hydrology, population, and industrial growth, and political and cultural history, reveals precisely how communities articulated their different understandings of pollution problems, as well as their distinct definitions of nuisance and means of coping with pollution. By identifying, at the local level, multiple representations of pollution phenomena and practices put forward to decontaminate water, we shed light on the difficulties surrounding the implementation of water treatment infrastructure in municipalities across Quebec between 1945 and 1980.